RISK LOCI FOR CHRONIC OBSTRUCTIVE DISEASE RESIDE ON CHROMOSOME 14: A CASE-CONTROL STUDY ON THE PAKISTANI POPULATION - Jan, Peerzada Fawad Ullah; Kousar, Samra; Mahmood, Atif; Nadeem, Sarooj; Malik, Kausar; Safir, Waqas; Shujaat, Nodia; Khan, Fahim Ullah; Shahid, Mariam (Journal of Ayub Medical College Abbottabad, 2023)
Background: Chronic Obstructive Pulmonary Disease (COPD), the third leading cause of death worldwide, is characterized by airflow limitation that can be due to abnormalities in the airway and/or alveoli. Genetic diagnosis at an early stage can be a key factor in the provision of accurate and timely treatment. Single Nucleotide polymorphisms (SNPs) are an important tool to study genetic association/ predisposition of the disease and have great potential to be diagnostic markers for early diagnosis of disease. Methods: This case-control COPD association study was designed for the five SNPs residing on potential candidate genes (SERPINA1, SERPINA3, RIN3), to check whether these genes are involved in the genetic predisposition for COPD in the Pakistani population or not. The SNAPshot method was used to find out the risk alleles and haplotypes using ABI Genetic analyzer 3130. GeneMapper, Haploview and PLINK 1.9 software were used for analyzing the genotypes and haplotypes taking smoking exposure and gender as covariates. Results: Two of the SNPs, rs4934 and rs17473 were found to be independently and significantly associated with COPD in our studied population whereas haplotype H1 for two SNPs, rs754388 and rs17473 (that are in high linkage disequilibrium), was found to be a significant risk factor for developing COPD symptoms. Conclusion: SNP variants of SERPINA1 and SERPINA3 are significantly and independently associated with COPD in the local population of Pakistan.